PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN KAIN TENUN DI DESA MASALILI KECAMATAN KUNTUNAGA KABUPATEN MUNA - Purnama, Muhamad Sunarno; Sukotjo, Endro; Yusuf, Hayat (-)
This study aims to determine the factors that influence product quality and price on consumer satisfaction in using masalili woven fabric in Muna Regency. The population of this study were consumers who had used masalili woven fabric products and the number was 95. The data collection method in this study was a questionnaire. The analytical method used is multiple linear regression analysis using the SPSS version 24 program.Â  The results of the study show that together price and product quality have a significant effect on consumer satisfaction. And partially the price has a significant effect on consumer satisfaction, product quality has an effect on consumer satisfaction,